Wychowanie do człowieczeństwa – jako przesłanie starszego pokolenia nauczycieli – w świetle ich pamiętników 2016 - Dróżka, Wanda (Rocznik Pedagogiczny, 2019)
The article attempts to familiarise the reader with the memoirs of teachers compiled as a result of the third edition of the National Competition for memoirs and other autobiographical statements under the title “Teacher’s message: Generations of Polish Teachers for the Future” (2014–2016). In the light of the preliminary analysis of the texts submitted, an outline emerges of the mission that teachers would see for themselves, for their successors, and for education of the 21st century. It is something significant: the mission of protecting humanity for future generations, for preserving the world, for the survival of spiritual values confronted with consumerism, cybertechnology, and scientific progress on the basis of genetics, computer science, etc. Education appears in the light of these diaries as a space and a way to reinforce humanity, which is threatened from different sides. There are two approaches here, two concepts of education and training, and of the teacher’s role in this work, the more conservative and the more liberal. In general, it is a question of rational citizenship, the rational use of subjectivity and autonomy, which is similar to M. Nussbaum’s con- cept of remedying the citizenship crisis. This mission of education requires reflective, subjective and autonomous teachers, using discursive reflexivity (thinking about their own thinking), with an analytical attitude, respecting the requirement of interdependence, understanding the contemporary world, themselves and others. In turn, what this requires from teachers is deep knowledge, thorough education, a high level of culture, and humanistic, subjective and reflective changes in their educa- tion and professional development.